Flash 5 Bible - Reinhardt, Robert (Wiley Publishing, 2011)
Enhanced and revised edition of the bestseller! 100% of what you need to know to learn and master the latest version of Macromedia Flash. Includes a CD-ROM packed with files from the book and valuable tryouts.